Development of Sport Kids Application as an Effort to Increase Physical Activity of Elementary School Children - Cheni Febrianti; Wildan Alfia Nugroho; Agus Mahendra (Universitas Negeri Semarang, 2025)
The increasing use of digital devices among children has led to decreased physical activity and increased sedentary lifestyles, posing serious health risks. This study aims to develop the Sport Kids application as an innovative digital platform to promote physical activity in elementary school children. Using the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate), the application was created with four main features: nutrition, physical activity, sports, and quizzes. It was designed using Canva and Scratch, then converted to Android format. Validation by media and material experts indicated an average feasibility score of 81%, categorized as very feasible. Implementation was carried out with 29 fourth-grade students over seven days. Physical activity levels were measured using the PAQ-C instrument before and after using the application. The results showed a significant improvement in activity levels. Statistical analysis using a paired sample t-test produced a significance value of 0.000 (p < 0.05), confirming that the Sport Kids application effectively increased children’s physical activity. This research concludes that digital applications, when properly designed and implemented, can serve as effective tools in promoting active and healthy lifestyles among school-aged children.